1997
DOI: 10.1007/bf01285562
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acute and chronic lithium on forskolin-induced reduction of rat activity

Abstract: Forskolin is a diterpene derivative that activates adenylate cyclase and raises cAMP levels in the cell. Both i.p. and i.c.v. forskolin cause behavioral hypoactivity. Lithium has been reported for many years to block cAMP accumulation, but the behavioral relevance of this biochemical effect is not clear. We studied the effect of acute and chronic lithium on icv forskolin-induced hypoactivity. Acute lithium had no effect, but chronic lithium significantly blocked forskolin-induced hypoactivity. The effect of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
1
1
0
1
Order By: Relevance
“…KNK 437 and GGA were dissolved in DMSO. No obvious adverse effect in rats was observed with stereotaxic injection of DMSO, which is consistent with other studies (Bersudsky et al, 1997;Chen et al, 2001;Xu et al, 2009). MB was dissolved in 0.9% saline.…”
Section: Drugssupporting
confidence: 70%
“…KNK 437 and GGA were dissolved in DMSO. No obvious adverse effect in rats was observed with stereotaxic injection of DMSO, which is consistent with other studies (Bersudsky et al, 1997;Chen et al, 2001;Xu et al, 2009). MB was dissolved in 0.9% saline.…”
Section: Drugssupporting
confidence: 70%
“…After decapitation brains were removed, frontal cortex specimens dissected and frozen at x80 xC until processed. The drug doses administrated were based upon previous studies in which it has been shown that these regimes result in rodent blood levels within the therapeutic range in patients (Bersudsky et al, 1997;Jardemark et al, 2000;Shaldubina et al, 2002;Shapiro et al, 2000). Haloperidol was from Janssen-Cilag (Raritan, NJ, USA), clozapine from Novartis (Basel, Switzerland) and LiCl and valproate were from Sigma (St. Louis, MO, USA).…”
Section: Drug Treatmentmentioning
confidence: 99%
“…Σν ιίζην ξπζκίδεη θαη ηα επίπεδα ηνπ θπθιηθνχ ΑΜΡ ζην ΚΝ, κεηψλνληάο ηα (Böer et al, 2008˙ Marmol, 2008˙ Montezinho et al, 2007˙ Wilting et al, 2007˙ Wang et al, 1999˙ Mori et al, 1996 ελψ πξφζθαηα εξεπλεηηθά δεδνκέλα ππνδεηθλχνπλ φηη ην θπθιηθφ ΑΜΡ ξπζκίδεηαη θαη απφ ηε δξαζηηθφηεηα ηεο GSK-3β, ε νπνία αλαζηέιιεηαη απφ ην ιίζην (Rao et al, 2010). Δπηπξνζζέησο, ε ρξφληα, αιιά φρη ε νμεία, ρνξήγεζε ιηζίνπ έρεη βξεζεί φηη αλαζηέιιεη ηελ επαγφκελε απφ θνξζθνιίλε 40 ππνδξαζηεξηφηεηα (Bersudsky et al, 1997 (Lee et al, 1999).…”
Section: δλδνθπηηάξην κνλνπάηη θπθιηθνύ αμρunclassified